Influence of Da'wah Content on TikTok on the Strengthening of Adolescent Moral Values - Ramadhani, Witri; Pratama, Farhan Fajar; Jamin, Ahmad (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the influence of da'wah content on TikTok on the strengthening of adolescent moral values. Using a quantitative approach, this study involved 31 adolescents in Kubang Agung Village as the sample. Data were collected through a questionnaire and analyzed using a simple regression test. The results show that da'wah content on TikTok has a significant influence on the strengthening of adolescent moral values, with a significance value of 0.001 (p 0.05). The coefficient of determination (R²) of 0.314 indicates that 31.4% of the variation in adolescent moral values can be explained by TikTok da'wah content, while the remaining 68.6% is influenced by other factors outside the study. Overall, this research concludes that TikTok can function as an effective da'wah medium, capable of conveying moral values creatively and in an easily accessible way for adolescents, provided it is used wisely and supported by a holistic moral education ecosystem.